HYBRID PHOTOVOLTAIC AND WIND POWER SYSTEM - Akshay Dhanawade; Abhijeet Mulik; Nikita Mane; Shweta Indalkar; Ashwini Nikam; Pratiksha Indalkar; Anup Pawshe (International Journal of Innovations in Engineering Research and Technology, 2022)
Renewable energy integration has attracted widespread attention due to its zero fuel cost, cleanliness, availability, and ease of installation. Among various renewable energy sources, photovoltaic (PV) and Wind turbines (WT) have become very attractive due to the abundant local availability in nature, Technological progress, and economic benefits. The hybrid combination of both distributed energy resources eliminates mutual intermittences due to their adverse nature, therefore, the reliability of the system will be improved. The basic key objective of the project is to generate electrical energy by using renewable and clean energy with minimum pollution.